A inserção dos imigrantes venezuelanos no sistema educacional do Recife e o acesso a educação na política migratória brasileira. - Batista, Bruno Amorim (2021)
In view of the considerable number of immigrants from the most diverse backgrounds in the city of Recife, there was a real sectorization of their organizations. If not, note that these immigrants are segregated in different areas of the city that, in turn, start to be recognized or, still, resignified by the origins of these immigrants. It is in this circumstance that the problem of educational exclusion of Venezuelan immigrants arises, due to the lack of social support and planning, of their insertion, and adequate adaptation, in the Brazilian educational system. The arrival of Venezuelan immigrants, from 2018, came from a humanitarian action of spatial fixation, but which was not accompanied by adequate planning by the local government in receiving these immigrants. The lack of public policies and planning makes it possible to maintain a cycle of violence, given that the violence suffered by these Venezuelan children, resulting from the lack of adequate school insertion, is reflected in a feeling of non-belonging that generates diseases such as depression, lack of interest in school, vulnerability to drug addiction, that is, a cycle of violence that distances him from better training and exposes him to greater social vulnerability. Thus, the study questioned if the existing public policies have promoted the adequate reception of Venezuelan immigrants in Recife, looking for the causes of this social marginalization. The research collected data on the insertion of Venezuelan school-age immigrants who arrived in Recife through the Acolhida Operation, with the support of the Pana project, and coordinated by the Brazilian NGO Caritas CNBB (northeast region 2), in the educational system place. The work raised public policies that were used in its favor, with the objective of verifying their utilization, pointing out, later, possible alternatives to the system currently used. The methodology consisted of collecting data on the enrollment, attendance and school performance of these immigrants, and the public policy tools that were eventually used in the process of insertion in the educational system, in order to verify whether the Brazilian State it has fulfilled its legal commitment, in offering social protection to Venezuelan immigrants, offering equal conditions of education with nationals. Finally, the research enable a scientific diagnosis of the social reality of Venezuelan immigrant students who arrived in Recife, suggesting a set of proposals that can support the development of an adequate public policy for the insertion of this immigrant in the Brazilian educational system.